2006
DOI: 10.1074/jbc.m508471200
|View full text |Cite
|
Sign up to set email alerts
|

A Splice Variant of Stress Response Gene ATF3 Counteracts NF-κB-dependent Anti-apoptosis through Inhibiting Recruitment of CREB-binding Protein/p300 Coactivator

Abstract: Activating transcription factor (ATF) 3 plays a role in determining cell fate and generates a variety of alternatively spliced isoforms in stress response. We have reported previously that splice variant ATF3⌬Zip2, which lacks the leucine zipper region, is induced in response to various stress stimuli. However, its biological function has not been elucidated. By using cells treated with tumor necrosis factor-␣ and actinomycin D or cells overexpressing ATF3⌬Zip2, we showed that ATF3⌬Zip2 sensitizes cells to apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 48 publications
3
32
0
1
Order By: Relevance
“…Previous studies have shown that ER recruitment to the CRH promoter is accompanied by an increase in H3 acetylation, as well as CBP recruitment (34). CBP has also been shown to be important for NF-B action on the BIRC3 gene (25). In MCF-7 breast cancer cells, CBP appears to be present constitutively at the BIRC3 promoter.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that ER recruitment to the CRH promoter is accompanied by an increase in H3 acetylation, as well as CBP recruitment (34). CBP has also been shown to be important for NF-B action on the BIRC3 gene (25). In MCF-7 breast cancer cells, CBP appears to be present constitutively at the BIRC3 promoter.…”
Section: Discussionmentioning
confidence: 97%
“…The observation that M2 induces viral gene expression in ganglia harboring latent virus and maintained in medium containing NGF plus EGF suggests that M2 acts as a dominant negative factor, possibly by interacting with a partner other than ATF3. As noted in the introductory section, ATF3 can form heterodimers with other members of ATF/CREB proteins (36,37). M2 contains the ZIP domain required for the formation of homodimers or heterodimers, but it does not interact with WT ATF3.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been described that a spliced variant of ATF-3 but not of the full-length ATF-3 sensitizes cells to apoptosis, partly by suppressing expression of NF-B-dependent antiapoptotic genes (47). Thus, we next defined by EMSA the NF-B activation in ATF3…”
Section: Atf-3 Is Involved In Pkr-inducedmentioning
confidence: 99%